Design and Development of an Innovation Model for the Opak Machine at Opak Ketan MSMEs Cibuaya Karawang using the House of Quality Method - Debora, Fransisca; Rahma, Rana Ardila; Nuraini, Umi; Rahmani, Hani Fitria (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
One of the MSMEs (Micro, Small Medium Enterprise) in the food sector located in Cibuaya Karawang area, namely Opak Ketan MSMEs, still carries out the opak production process manually, resulting in various shapes and diameters of opak. Opak ketan itself is made from a type of opak with different sizes and thicknesses, such as larger and thicker opak, and smaller opak with thin thickness and a crisp texture due to being baked. According to field analysis and interviews conducted at the research site, the manual production process presents difficulties and causes fatigue for workers, particularly in the formation of opak diameter and thickness. The printing process is done one by one (repeatedly), making it time-consuming and causing fatigue for workers who sit for long periods. As a result, the shape and thickness of opak lack precision (inconsistencies in size), leading to a lack of standardization. In terms of work activities, workers easily experience fatigue, particularly in their hands, waist, and back due to repetitive static movements. Ergonomically, working conditions are a factor that can enhance productivity, safety, and comfort for workers. Therefore, there is a need for the development and design of a suitable technology innovation model that can facilitate opak workers by creating a tool for printing opak ketan using an opak printing machine. This innovation can influence increased production capacity to be faster and standardized in shape and thickness. This design also applies the House of Quality (HOQ) model which successfully links consumer desires with a product design which produces 10 assumed criteria and 15 characteristics in order of importance. So it is concluded that the first priority that needs to be taken into account is determining price, flexibility and engine resources (fuel).